If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+5(-3)=-15
We simplify the equation to the form, which is simple to understand
3y+5(-3)=-15
Reorder the terms in parentheses
3y+(-15)=-15
Remove unnecessary parentheses
+3y-15=-15
We move all terms containing y to the left and all other terms to the right.
+3y=-15+15
We simplify left and right side of the equation.
+3y=0
We divide both sides of the equation by 3 to get y.
y=0
| G(2)=3t-7 | | 8(2+2)=4(2+1)-20 | | 9t+14-5t-7=29 | | m^2-30=7m | | 10x^2-12x-9=0 | | w/x=y/z | | 0.5x-3(40+x)=0.3(40) | | y+2(2)=1 | | 9/10x=27 | | y+2(-3)=1 | | -8+6x=34x+24 | | F^2-3r=28 | | 1/2m2+1/4n2 | | 2p-1/9 | | 144=-13(x+5) | | 0=6-6x | | 4x^4+36x^2=0 | | 9x-3=-2x-18 | | 7(4x+9)=6(11x-12) | | 7x(4x+9)=6(11x-12) | | -106-10x=9x+20 | | 3p+6m=3m-9 | | 8x-9y=-16 | | 9x-6=10x+12 | | 9(x+2)+6(x+6)=6x-6 | | 71.80=25+0.15 | | 4y+3y=11 | | -x-3y=-23 | | x+4-3x^2=0 | | 3-2x+x=5x-5+2x | | 8w-32=4w | | -7-x=3x+17 |